Analisis Kelayakkan Bisnis Kuliner dan Strategi Pemasaran pada Usaha Waroeng Spesial Sambal Yogyakarta - Mufti Afif; Isna Arifa (Universitas Alma Ata, 2018)
The process of business feasibility analysis is certainly closely related to the management of a business, which will analyze the prospects of market share, future prospects of the product especially to the appropriate marketing strategies to achieve the goals of a business. Waroeng SS is one of the culinary business unit known by the people in Yogyakarta area. This culinary business unit offers products that are different from other food stalls, sambal with various variants but still embed the characteristic of Javanese tongue. And now has earned billions of rupiah in turns per month, and outlets have reached 80 branches in the Java-Bali region. Therefore this paper should like to examine the business feasibility of SS owner in their begining and also to know about their product marketing strategy recently.The type of research in this work uses a qualitative approach by digging data through direct interviews, both to the management of Waroeng SS and some of its customers.The results conclude that business feasibility analysis is well planned; from the process of market determination, market segmentation, location, price and product have all been analyzed. While the marketing strategy which is done just make the customers trusty as their priority then they will certainly share the information to their colleagues.Keywords: Business Feasibility, Strategy, Marketing, Waroeng SS